Telavancin, a hope against Methicillin Resistant Staphylococcus aureus - Babar, Nazish (International Journal of Pathology, 2019)
Objective: To determine the in vitro efficacy of Telavancin against Methicillin resistant Staphylococcus aureus.Methods: This cross-sectional study was conducted at the Department of Microbiology, Army Medical College, Islamabad/Military Hospital, Rawalpindi, from 1st Nov 2012 to 30th June 2013. The authors aimed at assessing the in vitro efficacy of Telavancin against Methicillin resistant Staphylococcus aureus by E strip method as this study will be a help in determining guidelines for the interpretation of our local susceptibility breakpoint criteria for Telavancin against possibly emerging vancomycin intermediate Staphylococcus aureus and vancomycin resistant Staphylococcus aureus. Should vancomycin resistance become wide spread alternative therapies for methicillin resistant Staphylococcus aureus will be urgently needed.Results: In this study 102 methicillin resistant Staphylococcus aureus were isolated, and all were found to be 100% susceptible to Telavancin.Conclusion: Telavancin has excellent in vitro activity against methicillin resistant Staphylococcus aureus